2023
DOI: 10.1101/2023.10.13.562147
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The H3.3 K36M oncohistone disrupts the establishment of epigenetic memory through loss of DNA methylation

Joydeb Sinha,
Jan F. Nickels,
Abby R. Thurm
et al.

Abstract: SummaryHistone H3.3 is frequently mutated in cancers, with the lysine 36 to methionine mutation (K36M) being a hallmark of chondroblastomas. While it is known that H3.3K36M changes the cellular epigenetic landscape, it remains unclear how it affects the dynamics of gene expression. Here, we use a synthetic reporter to measure the effect of H3.3K36M on silencing and epigenetic memory after recruitment of KRAB: a member of the largest class of human repressors, commonly used in synthetic biology, and associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 95 publications
0
1
0
Order By: Relevance
“…H3K36me2 may also play a role in heterochromatin reorganization in embryogenesis mediated through the perinucleolar ring-shaped structures at the 2-cell stage to more typical chromocenters at the later stages. A very recent study has shown a model that H3K9me3 and H3K36 methylation tandemly promote DNA methylation (Sinha et al, 2023). DNA methylation in oocytes is also regulated by H3K36me2 and H3K36me3 (Yano et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…H3K36me2 may also play a role in heterochromatin reorganization in embryogenesis mediated through the perinucleolar ring-shaped structures at the 2-cell stage to more typical chromocenters at the later stages. A very recent study has shown a model that H3K9me3 and H3K36 methylation tandemly promote DNA methylation (Sinha et al, 2023). DNA methylation in oocytes is also regulated by H3K36me2 and H3K36me3 (Yano et al, 2022).…”
Section: Discussionmentioning
confidence: 99%